The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Better be reactive at the beginning. Implications of the first seconds of an encounter for the tutoring style in human-robot-interaction - Pitsch, Karola; Lohan, Katrin Solveig; Rohlfing, Katharina; Saunders, Joe; Nehaniv, Chrystopher L.; Wrede, Britta (Proceedings of the 21TH IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN 2012))
The paper investigates the effects of a robot’s “on-line” feedback during a tutoring situation with a human tutor. Analysis is based on a study conducted with an iCub robot that autonomously generates its feedback (gaze, pointing gesture) based on the system’s perception of the tutor’s actions using the idea of reciprocity of actions. Sequential micro-analysis of two opposite cases reveals how the robot’s behavior (responsive vs. non-responsive) pro-actively shapes the tutor’s conduct and thus co-produces the way in which it is being tutored. A dialogic and a monologic tutoring style are distinguished. The first 20 seconds of an encounter are found to shape the user’s perception and expectations of the system’s competences and lead to a relatively stable tutoring style even if the robot’s reactivity and appropriateness of feedback changes.

Nonlocal Imaging by Conditional Averaging of Random Reference Measurements - Luo, Kai Hong; Huang, Bo-Qiang; Zheng, Wei-Mou; Wu, Ling-An (Chinese Physics Letters)

Textural analysis of optical scattering for identification of cancer in breast surgical specimens - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (IEEE 9th International Symposium on Biomedical Imaging)
Textural analysis of tissue scattering images is proposed for healthy versus tumor discrimination. Scattering center density varies from normal to tumor tissues and this variation is translated into different textures in the scattering power map. Adipose tissue shows low autocorrelation values while tumor tissues present higher entropies than normal tissue. Consequently, a combination of autocorrelation and entropy values allows ready tissue discrimination by a supervised linear classifier. The proposed approach has been validated over a set of 29 breast tissue samples achieving a sensitivity of 73.59% and specificity of 82.40%.

ICA-guided delineation of breast cancer pathology - Eguizabal, Alma; Laughney, Ashley M.; Garcia-Allende, P. Beatriz; Krishnaswamy, Venkataramanan; Wells, Wendy A.; Paulsen, Keith D.; Pogue, Brian W.; Lopez-Higuera, Jose M.; Conde, Olga M. (IEEE 9th International Symposium on Biomedical Imaging)
A surgeon-guided independent component analysis from optical reflectance measurements is proposed for breast tumor delineation. Independent Component Analysis is first applied to extract the most relevant features from local measures of broadband reflectance and then a tumor probability indicator is obtained and provided utilizing surgeon assistance to resolve the inherent ambiguities in the independent component calculation. A set of 29 breast tissue samples have been diagnosed achieving a sensitivity of 90.57%, and specificity of 93.98%.

Diva – Die Inszenierung der übermenschlichen Frau. Interdisziplinäre Untersuchungen zu einem kulturellen Phänomen des 19. und 20. Jahrhunderts. Hrsg. von Rebecca Grotjahn, Dörte Schmidt und Thomas Seedorf. Schliengen: Edition Argus 2011. 275 S., Abb., Nbsp. (Forum Musikwis-senschaft. Band 7.) - Tumat, Antje (Die Musikforschung)

Mesoporöse Silica - Moderne Funktionsmaterialien im Chemieunterricht - Wilke, Timm; Haffer, Stefanie; Tiemann, Michael; Waitz, Thomas (CHEMKON)
Poröse Funktionsmaterialien wie halbleitende Metalloxide, Kohlenstoff-Formen oder auch Silica werden aktuell von verschiedenen Wissenschaftsdisziplinen intensiv für Bereiche der Energiespeicherung, Sensorik, Katalyse und Stofftrennung erforscht. Im Beitrag werden schwerpunktmäßig geordnet-mesoporöse Silica-Materialien behandelt, die seit etwa 20 Jahren synthetisch zugänglich sind. Neben den Grundlagen der Herstellung über ein Templat-Verfahren werden im Beitrag auch drei Experimente vorgestellt, die im Chemieunterricht oder Schülerlabor durchgeführt werden können. Zudem wird gezeigt, dass sich verschiedene Aspekte aus dem Kompetenzbereich Fachwissen mit Hilfe des Themas „Mesoporöse Silica“ miteinander vernetzen lassen.

Die Ordnung der (Nicht)Orte. Kampnagel und Kreativwirtschaft - Degeling, Jasmin (Performing Politics. Politisch Kunst machen nach dem 20. Jahrhundert)

Sovereign risk and bank-specific CDS pricing - Uhde, André; Michalak, Tobias; Meine, Christian
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.

Der Kuss, ein Päckchen und der Spiegel. Zur Rhetorik der Authentizität - oder wer sieht wen eigentlich wie an? - Janus, Richard (Scripts, Fiktionen, Konstruktionen. Theologische, kirchliche und popkulturelle Anmerkungen zu Reality-TV und gefühlsechtem Leben)

1.-3. Johannesbrief - Janus, Richard (Religionspädagogischer Kommentar zur Bibel)

Das Praxissemester in der Ausbildungsregion der Universität Paderborn. Vortrag im Rahmen des Symposions: Das neue Grundschullehramt in NRW an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik in der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. Universität Paderborn - Büker, Petra; Berning, Hanna
September 2011

Sichtweisen, Handlungslogiken und Belastungserleben von Grundschullehrer/innen im Umgang mit kultureller Vielfalt: Forschungsbefunde aus der Paderborner Professionsstudie Pro-LEG. Vortrag an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik in der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. Universität Paderborn - Büker, Petra; Hüpping, Birgit
September 2011

Schul- und Kindergartenentwicklung als neues interdisziplinäres Forschungsfeld: Methodologische Herausforderungen am Beispiel des Paderborner Modellprojektes "Kinderbildungshaus". Vortrag an der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaften. Universität Paderborn - Büker, Petra; Bührmann, Thorsten; Kordulla, Agnes
September 2011

A Test Bed for Investigating Self-X Properties in Multi-Robot Societies - Jungmann, Alexander; Lutterbeck, Jan; Werdehausen, Benjamin; Kleinjohann, Bernd (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
In this paper, we introduce a test bed for demonstrating and investigating self-x properties, such as self-optimization and self-organization, within the scope of multi-robot societies under realistic conditions. By doing so, we shift the investigation and demonstration of biologically inspired mechanisms from the simulative point of view to a dynamic and more complex realistic environment. For this purpose, we developed a controlled real-world environment to overcome common problems such as self-localization. Furthermore, we elaborated a concept for a descriptive robotic real-world game. By means of this game, we provide an instrument, which is easily accessible for any kind of audience on the one hand, while it still leaves enough space for an extensive scientific investigation on the other hand.

Miniature Robot BeBot: Mechatronic Test Platform for Self-X Properties - Gausemeier, Jürgen; Schierbaum, Thomas; Dumitrescu, Roman; Herbrechtsmeier, Stefan; Jungmann, Alexander (Proceedings of the 9th IEEE International Conference on Industrial Informatics (INDIN))
Machines are omnipresent. They produce, they transport. Machines facilitate work and assist. The increasing penetration of mechanical engineering by information technology enables considerable benefits. We refer to such systems as advanced mechatronic systems, which relay on the close interaction of mechanics, electric/electronics, control engineering and software engineering. Hence, the design and production of such systems is an interdisciplinary and complex task. Our ambition is a new school for the design of advanced mechatronic systems. Consequently, we need an avant-garde basic system which can be used to develop and to test future applications. The miniature robot BeBot is such a basic system. This robot constitutes the test bench for the applications, being based on modern approaches, such as self-optimization, self-organization and self-coordination as well as on the use of new manufacturing technologies.

Comparison of periodic and aperiodic task models for cyber-physical-systems - Thuy, Andreas (Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC), 2011 6th International Workshop on)

Validation of protein and potassium intakes assessed from 24 h recalls against levels estimated from 24 h urine samples in children and adolescents of Turkish descent living in Germany: results from the EVET! Study - Bokhof, Beate; Buyken, Anette; Doğan, Canan; Karaboğa, Arzu; Kaiser, Josa; Sonntag, Antje; Kroke, Anja (Public Health Nutrition)
Abstract Objective Nutrition-related health problems such as obesity are frequent among children and adolescents of Turkish descent living in Germany, yet data on their dietary habits are scarce. One reason might be the lack of validated assessment tools for this target group. We therefore aimed to validate protein and K intakes from one 24 h recall against levels estimated from one 24 h urine sample in children and adolescents of Turkish descent living in Germany. Design Cross-sectional analyses comprised estimation of mean differences, Pearson correlation coefficients, cross-classifications and Bland–Altman plots to assess the agreement between the nutritional intake estimated from a single 24 h recall and a single 24 h urine sample collected on the previous day. Setting Dortmund, Germany. Subjects Data from forty-three study participants (aged 5–18 years; 26 % overweight) with a traditional Turkish background were included. Results The 24 h recall significantly overestimated mean protein and K intake by 10·7 g/d (95 % CI of mean difference: 0·6, 20·7 g/d) and 344 mg/d (95 % CI 8, 680 mg/d), respectively. Correlations between intake estimates were r = 0·25 ( P = 0·1) and 0·31 ( P = 0·05). Both methods classified 70 % and 69 % of the participants into the same/adjacent quartile of protein and K intake and misclassified 7 % and 7 %, respectively, into the opposite quartile. Bland–Altman plots indicated a wide scattering of differences in both protein and K intake. Conclusions Among children and adolescents of traditional Turkish descent living in Germany, one 24 h recall may only be valid for categorizing subjects into high, medium or low consumers.

Verifying Linearisability with Potential Linearisation Points - Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (FM 2011: Formal Methods - 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings)

PM-IRRAS studies of the adsorption and stability of organophosphonate monolayers on passivated NiTi surfaces - Maxisch, M.; Ebbert, Christoph; Torun, B.; Fink, N.; de los Arcos, T.; Lackmann, J.; Maier, H. J.; Grundmeier, Guido (APPLIED SURFACE SCIENCE)
Alkylphosphonic acids of different alkyl chain lengths were adsorbed on electrochemically polished NiTi surfaces from ethanolic solutions. The electropolishing process led to passive films mainly composed of Ti-oxyhydroxide. The surface showed nanoscopic etching pits with a depths of about 2 nm and a diameter of about 20 nm. The interfacial binding mechanism of the phosphonic acid group to the oxyhydroxide surface and the ordering of the monolayer were spectroscopically analysed by means of infrared reflection absorption FTIR-spectroscopy with (PM-IRRAS) and without (IRRAS) photoelastic modulation. The comparison of IRRAS and PM-IRRAS data of the long chain octadecylphosphonic acid monolayer proved that the binding mechanism of the phosphonic acid group to the oxyhydroxide surface is based on a mono-or bidentate bond, which is not stable in the presence of high water activities. An alkyl chain length of 17 CH2 groups is required for the formation of self-assembled monolayers, which are stable in aqueous environments. These long chain aliphatic organophosphonic acid monolayers were shown to inhibit anodic and cathodic surface reactions. (C) 2010 Elsevier B.V. All rights reserved.

Vom Studiolo zur virtuellen Forschungsumgebung - Brennecke, Andreas; Oevel, Gudrun; Strothmann, A. (4. DFN-Forum Kommunikationstechnologien – Beiträge der Fachtagung 20./21.6.2011 Bonn)

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)

Hashed Patricia Trie: Efficient Longest Prefix Matching in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (WALCOM: Algorithms and Computation - 5th International Workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011. Proceedings)

Parallel Out-of-Core Occlusion Culling - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm
We present a parallel rendering system for PC-Clusters to visualize large 3D scenes. One single visualization node, equipped with a high-end graphics adapter, is supported by a group of backend nodes with weak graphics performance. The objects of the scene are distributed among these backend nodes, they serve two purposes: First, they provide an out-of-core memory system for the visualization node. Second, they assist the visualization node's rendering by performing visibility calculations and only sending visible objects to the visualization node. In order to obtain fast rendering with our system, we have to distribute the objects among the backend nodes in a way that does not only guarantee an even distribution of the objects, but also an even distribution of the visibility calculations and the amount of data send to the visualization node. We identify necessary properties of the distribution and argue that a random distribution is a good candidate. Further, in order to reduce the number of objects sent to the visualization node per frame, we employ an approximate hierarchical occlusion culling in each backend node. For this, they are equipped, in addition to the objects assigned to them, with simplified versions of the other objects of the 3D scene. The visualization node is equipped with 512 MiB video memory and supported by 15 backend nodes. This system is able to render a approx. 350 million polygons (approx. 8.5 GiB) large aircraft model between 20 - 30 fps and thus allows a walkthrough in real-time.

Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings

Multihop Performance of Cooperative Preamble Sampling MAC(CPS-MAC) in Wireless Sensor Networks - Azeem M. Khan, Rana; Karl, Holger (Ad-hoc, Mobile, and Wireless Networks - 10th International Conference, ADHOC-NOW 2011, Paderborn, Germany, July 18-20, 2011. Proceedings)

Coding Opportunities from Similar Data in Wireless Cooperation Diversity Systems - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (IEEE 8th International Conference on Mobile Adhoc and Sensor Systems, MASS 2011, Valencia, Spain, October 17-22, 2011)

Backhaul network pre-clustering in cooperative cellular mobile access networks - Biermann, Thorsten; Scalia, Luca; Choi, Changsoon; Karl, Holger; Kellerer, Wolfgang (12th IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks, WOWMOM 2011, Lucca, Italy, 20-24 June, 2011)

User Centered Design Process of OSAMi-D - Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Senft, Björn; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (HEALTHINF 2011 - Proceedings of the International Conference on Health Informatics, Rome, Italy, 26-29 January, 2011)

Editorial bwp@ 20 - Tramm, T.; Kremer, H.-Hugo; Tenberg, R. (bwp@ Ausgabe 20, Lernfeldansatz 15 Jahre danach)

Kooperationsvorhaben ‚berufliches Gymnasium‘ und Bachelor Wirtschaftswissenschaften. Ein Paderborner Modellprojekt zur Berufs- und Studienorientierung - Kremer, H.-Hugo; Sandmann, D. (bwp@ Spezial 5 - Hochschultage Berufliche Bildung 2011, Workshop 29)

Operating principle of a shadowed c-Si solar cell in PV modules - Wendlandt, S.; Drobisch, A.; Tomow, D.; Friedrichs, M.; Krauter, Stefan; Grunow, Paul (Proceedings of the ISES Solar Word Congress)

PV Module Lamination Durability - Krauter, Stefan; Pénidon, Romain; Lippke, Benjamin; Hanusch, Matthias; Grunow, Paul (Proceedings of the ISES Solar Word Congress 2011)

Wallenstein in der deutschsprachigen Erzählliteratur des 19. und 20. Jahrhunderts - Süßmann, Johannes (Wallensteinbilder im Widerstreit. Eine historische Symbolfigur in Geschichtsschreibung und Literatur vom 17. bis zum 20. Jahrhundert)

FrauenMusikRäume – Orte von Frauen in der urbanen Musikkultur. Einleitung - Grotjahn, Rebecca (Musik in Leipzig, Wien und anderen Städten im 19. und 20. Jahrhundert: Verlage – Konservatorien – Salons – Vereine – Konzerte)

The most popular woman in the world – die Diva und die Anfänge des Starwesens im 19. Jahrhundert - Grotjahn, Rebecca (Diva – Die Inszenierung der übermenschlichen Frau. Interdisziplinäre Untersuchungen zu einem kulturellen Phänomen des 19. und 20. Jahrhunderts)

Alltag im Innenraum: Die ‚Höhere Tochter‘ am Klavier - Grotjahn, Rebecca (Musik in Leipzig, Wien und anderen Städten im 19. und 20. Jahrhundert: Verlage – Konservatorien – Salons – Vereine – Konzerte)

Evaluation eines Förderprogramms zur Entwicklung wortschatzbasierter Lesestrategien bei Kindern in der Grundschule. Posterpräsentation auf der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Fichlter, Philip; Förster, Sabrina; Niebuhr-Siebert, Sandra; Nowak, Miriam; Hellmich, Frank

Selbstwirksamkeitsüberzeugungen und Hilflosigkeitserleben bei Lehramtsstudentinnen und -studenten im Zusammenhang mit ihren Diagnosekompetenzen. Vortrag auf der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Berger, Jennifer; Hellmich, Frank

Moderation des Symposiums „Förderung von Kindern mit Migrationshintergrund im Vor- und Grundschulbereich“. 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Koch, Katja; Hellmich, Frank

Qualitative und quantitative Forschungsmethoden in der Grundschulforschung. Eingangsreferat zum Nachwuchsworkshop auf der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Hellmich, Frank; Fricke, Katharina

Förderung der Lesekompetenz durch ein wortschatzbasiertes Lesestrategietraining bei Kindern mit Deutsch als Zweitsprache. Vortrag auf der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Förster, Sabrina; Niebuhr-Siebert, Sandra; Hellmich, Frank

Erfassung fachdidaktischer Kompetenzen angehender Grundschullehrkräfte – Ergebnisse aus einem empirischen Forschungsprojekt. Vortrag auf der 20. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik) - Hoya, Fabian Karl; Hellmich, Frank

Soziale Brennpunkte - Landhäußer, Sandra (Lexikon Erziehungswissenschaft)
Erziehungswissenschaft ist eine in mehreren Schritten in Deutschland seit Ende des 18. Jahrhunderts entstandene, definitiv seit Anfang des 20. Jahrhunderts etablierte wissenschaftliche Disziplin, die gegenwärtig meist zu den Sozialwissenschaften gerechnet wird. Ihr Gegenstand ist eine Praxis, die mit Grundbegriffen identifiziert wird, zu denen immer Erziehung und Bildung einschließlich Unterricht gehören, oft durch Sozialisation und andere Begriffe aus anderen Disziplinen erweitert. Ihre Methoden entstammen den Geistes- und Sozialwissenschaften.

Stimmbesitzer und Sängerdarsteller. Die Inszenierung des Singens auf der Musiktheater-Bühne in den ersten Jahrzehnten des 20. Jahrhunderts - Grotjahn, Rebecca (Frankfurter Zeitschrift für Musikwissenschaft)

Diva – Die Inszenierung der übermenschlichen Frau. Interdisziplinäre Untersuchungen zu einem kulturellen Phänomen des 19. und 20. Jahrhunderts

Photocatalytic ozone sensor based on mesoporous indium oxide: Influence of the relative humidity on the sensing performance - Wagner, T.; Hennemann, J.; Kohl, C.-D.; Tiemann, Michael (Thin Solid Films)
Mesoporous In2O3, synthesized by a nanocasting procedure, is used as a resistive gas sensor for ozone in very low concentrations (from 20 ppb to 2.4 ppm) at room temperature. Its sensing performance is substantially increased by illumination with blue light (460 nm, 2.7 eV). For low ozone concentrations the sensor response increases with increasing humidity. However, higher humidity also results in the occurrence of a saturation of the response at lower ozone concentrations; this is rationalized by assuming a poisoning of surface active sites by hydroxyl groups.

Neurophysiologische Korrelate der Wahrnehmungs-Handlungs-Kopplung am Beispiel des leichtathletischen Hochsprungs - Koester, D.; Güldenpenning, Iris; Schack, T. (Kreativität – Innovation – Leistung. 20. dvs- Hochschultag)

»Wo solche sind wie du – da ist der sieg.« Preußentum, Katholizismus und ein ›katholischer Preuße‹ im George-Kreis - Gretz, Daniela (Preußische Katholiken und katholische Preußen im 20. Jahrhundert.)

§§ 20 bis 23 UmwStG: Die Einbringung von Unternehmensteilen in eine Kapitalgesellschaft - Ansatz von Buchwerten oder gemeinen Werten - Maßbaum, Alexandra; Sureth-Sloane, Caren (Steuer und Studium)

Aerosol synthesis of silicon nanoparticles with narrow size distribution—Part 1: Experimental investigations - Körmer, R.; Jank, M.P.M.; Ryssel, H.; Schmid, Hans-Joachim; Peukert, W. (Journal of Aerosol Science)
A study on the feasibility of aerosol processing of nearly monodisperse silicon nanoparticles via pyrolysis of monosilane in a hot wall reactor is presented. For optimal conditions silicon nanoparticles with a geometric standard deviation of 1.06 were synthesized at a production rate of 0.7 g/h. The size of the particles could be precisely controlled in the range of 20–40 nm, whilst maintaining a geometric standard deviation in the range of 1.06–1.08, by proper choice of the governing parameters temperature, residence time and precursor concentration. The results show that narrow particle size distributions can only be obtained in the temperature range between 900 and 1100 °C, as long as both the initial silane concentration (1 mbar silane partial pressure) and the reactor total pressure are low (25 mbar). This regime for the production of narrow particle size distributions has not been identified in prior work on the thermal decomposition of silane. Narrowly distributed particles can be obtained under conditions where nucleation and particle growth are separated and the agglomeration rates are negligible.

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

{SLAB:} A Certifying Model Checker for Infinite-State Concurrent Systems - Dräger, Klaus; Kupriyanov, Andrey; Finkbeiner, Bernd; Wehrheim, Heike (Tools and Algorithms for the Construction and Analysis of Systems, 16th International Conference, TACAS 2010, Held as Part of the Joint European Conferences on Theory and Practice of Software, ETAPS 2010, Paphos, Cyprus, March 20-28, 2010. Proceedings)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Reentrant superconductivity in superconductor/ferromagnetic-alloy bilayers - Zdravkov, V. I.; Kehrle, J.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Krug von Nidda, H.-A.; Lindner, Jörg; Moosburger-Will, J.; Nold, E.; Morari, R.; Ryazanov, V. V.; et al. (Physical Review B)
We studied the Fulde-Ferrell-Larkin-Ovchinnikov-type state established due to the proximity effect in superconducting Nb/Cu_41Ni_59 bilayers. Using a special wedge-type deposition technique, series of 20–35 samples could be fabricated by magnetron sputtering during one run. The layer thickness of only a few nanometers, the composition of the alloy, and the quality of interfaces were controlled by Rutherford backscattering spectrometry, high-resolution transmission electron microscopy, and Auger spectroscopy. The magnetic properties of the ferromagnetic alloy layer were characterized with superconducting quantum interference device magnetometry. These studies yield precise information about the thickness and demonstrate the homogeneity of the alloy composition and magnetic properties along the sample series. The dependencies of the critical temperature on the Nb and Cu41Ni59 layer thickness, T_c(d_S) and T_c(d_F), were investigated for constant thickness d_F of the magnetic alloy layer and d_S of the superconducting layer, respectively. All types of nonmonotonic behaviors of T_c versus d_F predicted by the theory could be realized experimentally, from reentrant superconducting behavior with a broad extinction region to a slight suppression of superconductivity with a shallow minimum. Even a double extinction of superconductivity was observed, giving evidence for the multiple reentrant behavior predicted by theory. All critical temperature curves were fitted with suitable sets of parameters. Then, T_c(d_F) diagrams of a hypothetical ferromagnet/superconductor/ferromagnet spin-switch core structure were calculated using these parameters. Finally, superconducting spin-switch fabrication issues are discussed in detail in view of the achieved results.

An Analysis of Literature Reviews on IS Business Value: How Deficiencies in Methodology and Theory Use Resulted in Limited Effectiveness - Schryen, Guido (Proceedings of the First Scandinavian Conference on Information Systems (SCIS))
Enduring doubts about the value of IS investments reveal that IS researchers have not fully managed to identify and to explain the economic benefits of IS. This paper assumes that literature reviews, which represent a powerful instrument for the identification and synthesis of knowledge, have not tapped their full potential to address this issue due to deficiencies in methodology. The analysis of 18 literature reviews published in pertinent academic outlets during the past 20 years shows such deficiencies. Two of the most critical weaknesses identified are (1) the lack of theory use in most reviews and (2) a weak linkage of reviews, resulting in little progress in theory and framework development. The systematic identification of these weaknesses and the extraction of promising methodological examples from past literature are the main contributions of this work, which supports the composition of more effective literature reviews in future research.
Keywords: Literature review; Business value; Information systems; Methodology; Theory

Operation management of offshore wind farms by echo state networks - Bendfeld, Jörg; Splett, Michael; Krieger, J.; Kobialka, Hans-Ulrich; Schulz, Viktor (2010 European Wind Energy Conference and Exhibition (EWEC), April 20-23, 2010, Warsaw, Poland)

Energy feed characteristics of offshore wind farms – a modeled analysis of single and clustered farms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Reducing the offshore wind farm feed-in fluctuations by fast reacting biogas plants - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Measurements for wave and current modeling regarding offshore-windfarms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Advanced,multipurpose offshore-metmast - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Variations of pricing at energy markets caused by energyfeed of offshore wind farms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Der Kindergarten als Sprachlernort: Pragmatisch - kommunikative Aspekte des Spracherwerbs in Kindertageseinrichtungen. Kongressbeitrag zum 29. Kongress der Deutschen Gesellschaft für Sprachheilpädagogik - Albers, Timm (Disziplinen im Dialog)

Integration auf den allgemeinen Arbeitsmarkt bei geistiger Behinderung: Utopie oder Perspektive - Laubenstein, Désirée; Heger, M. (In: Lernen konkret, 29. Jahrgang, Nr. 2)

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
GaAs-based semiconductor microdisks with high quality whispering gallery modes (Q44000) have been fabricated.A layer of self-organized InAs quantumdots (QDs) served as a light source to feed the optical modes at room temperature. In order to achieve frequency tuning of the optical modes, the microdisk devices have been immersed in 4 – cyano – 4´-pentylbiphenyl (5CB), a liquid crystal(LC) with a nematic phase below the clearing temperature of TC≈34°C .We have studied the device performance in the temperature rangeof T=20-50°C, in order to investigate the influence of the nematic–isotropic phase transition on the optical modes. Moreover,we havea pplied an AC electric field to the device,which leads in the nematic phase to a reorientation of the anisotropic dielectric tensor of the liquid crystal.This electrical anisotropy can be used to achieve electrical tunability of the optical modes.Using the finite-difference time domain (FDTD) technique with an anisotropic material model, we are able to describe the influence of the liquid crystal qualitatively.
Keywords: tet_topic_qd; tet_topic_microdisk

An integrated 0.6–4.6 GHz, 5–7 GHz, 10–14 GHz, and 20–28 GHz frequency synthesizer for software-defined radio applications - Osmany, Sabbir A.; Herzel, Frank; Scheytt, J. Christoph (IEEE Journal of Solid-State Circuits)

Kleine deutsche Museumsgeschichte: von der Aufklärung bis zum frühen 20. Jahrhundert - Hartung, Olaf

Melanie Hong: Gewalt und Theatralität in Dramen des 17. und des späten 20. Jahrhunderts. Untersuchungen zu Bidermann, Gryphius, Weise, Lohenstein, Fichte, Dorst, Müller und Tabori. Würzburg: Königshausen & Neumann, 2008 - Eke, Norbert Otto (Germanistik)

Measure, Diagnose, Refactor: A Formal Quality Cycle for Software Models - Ruhroth, Thomas; Voigt, Hendrik; Wehrheim, Heike (35th Euromicro Conference on Software Engineering and Advanced Applications, SEAA 2009, Patras, Greece, August 27-29, 2009, Proceedings)

A new FFQ designed to measure the intake of fatty acids and antioxidants in children - Stiegler, Petra; Sausenthaler, Stefanie; Buyken, Anette; Rzehak, Peter; Czech, Daniel; Linseisen, Jakob; Kroke, Anja; Gedrich, Kurt; Robertson, Claire; Heinrich, Joachim (Public Health Nutrition)
Abstract Objective The present paper describes the systematic development of an FFQ to assess the intake of fatty acids and antioxidants in school-aged children. In addition, a validation study applying 24 h dietary recalls was performed. Design Using the variance-based Max_r method, a list of eighty-two foods was compiled from data obtained by 3 d weighed dietary records. The foods were used to design an FFQ, the comprehensibility of which was evaluated in a feasibility study. In addition, the FFQ was validated in a subset of 101 children from the German Infant Nutritional Intervention Study (GINI PLUS) against one 24 h dietary recall. Results The feasibility study attested a good acceptance of the FFQ. Mean intake of foods compared well between the FFQ and the 24 h dietary recall, although intake data generated from the FFQ tended to be higher. This difference became less apparent at the nutrient level, although the estimated average consumption of arachidonic acid and EPA using the FFQ still exceeded values recorded with the 24 h recall method by 45 % and 29 %, respectively. Conclusions On the basis of the systematic selection process of the food list, the established practicability of the FFQ and the overall plausibility of the results, the use of this FFQ is justified in future epidemiological studies.

Semi-automated Test Planning for e-ID Systems by Using Requirements Clustering - Güldali, Baris; Funke, Holger; Jahnich, Michael; Sauer, Stefan; Engels, Gregor (24th IEEE/ACM International Conference on Automated Software Engineering (ASE 2009), 16-20 November 2009, Auckland, New Zeland)
In acceptance testing, customer requirements as specified in system specifications have to be tested for their successful implementation. This is a time-consuming task due to inherent system complexity and thus a large number of requirements. In order to reduce efforts in acceptance testing, we introduce a novel approach that exploits redundancies and implicit relations in requirements specifications, which are based on multi-viewpoint techniques, in our case the reference model for open distributed processing (RM-ODP). It deploys requirements clustering and linguistic analysis techniques for reducing the total number of test cases. We report on concrete experiences with this approach within joint R&D work of the Software Quality Lab (s-lab) of the University of Paderborn and HJP Consulting, an international consulting company, specialized in planning, procurement and acceptance testing of national electronic identification (e-ID) systems. The paper is concluded with an overview on the current tool support especially for automated detection of the redundancies and implicit relations in requirements. Also the future work on the tool support for the overall test specification process is discussed.

The Gain of Overbooking - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing, 14th International Workshop, JSSPP 2009, Rome, Italy, May 29, 2009. Revised Papers)

GaN-based LEDs grown on 6-inch diameter Si (111) substrates by MOVPE - Zhu, D.; McAleese, C.; McLaughlin, K. K.; Häberlen, M.; Salcianu, C. O.; Thrush, E. J.; Kappers, M. J.; Phillips, W. A.; Lane, P.; Wallis, D. J.; Martin, T.; Astles, M.; et al. (Light-Emitting Diodes: Materials, Devices, and Applications for Solid State Lighting XIII)
The issues and challenges of growing GaN-based structures on large area Si substrates have been studied. These include Si slip resulting from large temperature non-uniformities and cracking due to differential thermal expansion. Using an AlN nucleation layer in conjunction with an AlGaN buffer layer for stress management, and together with the interactive use of real time in-situ optical monitoring it was possible to realise flat, crack-free and uniform GaN and LED structures on 6-inch Si (111) substrates. The EL performance of processed LED devices was also studied on-wafer, giving good EL characteristics including a forward bias voltage of ~3.5 V at 20 mA from a 500 μm x 500 μm device.

Kollektive Früherziehung und individuelle Bildungsbegleitung: Entwicklungsperspektiven für ein gesamtdeutsches Krippensystem - Albers, Timm (20 Jahre Mauerfall)

Kollektive Früherziehung und individuelle Bildungsbegleitung: Entwicklungsperspektiven für ein gesamtdeutsches Krippensystem - Albers, Timm (20 Jahre Mauerfall)

Medien und Medialität des Epischen in Literatur und Film des 20. Jahrhunderts: Bertolt Brecht – Uwe Johnson – Lars von Trier - van Laak, Lothar

My Mother: My Best Friend? Adults’ Relationships with Significant Others Across the Lifespan - Buhl, Heike M. (Journal of Adult Development)
In order to investigate the significance of adults’ relationship to their parents, this relationship is compared to relationships with siblings, friends, partners, and children. German adults (N = 902) between the ages of 20 and 86 completed the Network of Relationships Inventory (Furman and Buhrmester 1992). Participants felt most supported by their partners, followed by their children, mothers, friends, fathers, and siblings. Conflicts were more frequently found within the family (especially with the partner, followed by children, mothers, fathers, and siblings) than with friends. Except for partner relationships, both conflict and support decreased with age. Concerning relative power within their relationships, partners, mothers, and siblings are seen as equals, friends and especially fathers are perceived as more powerful, and children as less, yet increasingly powerful. Regarding all relationship types and relationship qualities, the differences between women and men were small.
Keywords: Family; Friends; Support; Conflict; Power

9.5 Gbit/s 20 Channel 1:8 DEMUX for a Coherent Optical Receiver DSPU ASIC Input Interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Woedehoff, Christian; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

9.5 Gbit/s 20 Channel 1:8 DEMUX for a Coherent Optical Receiver DSPU ASIC Input Interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Woedehoff, Christian; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

9.5 Gbit/s 20 channel 1∶8 DEMUX for a coherent optical receiver DSPU ASIC input interface - Herath, Vijitha R.; Adamczyk, Olaf; Peveling, Ralf; Wödehoff, Christian; Noé, Reinhold (2009 International Conference on Industrial and Information Systems (ICIIS))

Biblische Bilder - Beobachtungen zur Transformation der Bibel in der Klaviermusik in Deutschland im 19. und 20. Jahrhundert - Schroeter-Wittke, Harald (Inszenierungen der Heiligen Schrift. Jüdische und christliche Bibeltransformationen vom Mittelalter bis in die Moderne)

Ontology-Based Rescue Operation Management Technology for Emergency Response - Konstantopoulos, Stasinos; Pottebaum, Jens; Schon, Jochen; Schneider, Daniel; Winkler, Thomas; Paliouras, Georgios; Koch, Rainer (Mobile Response, Second International Workshop on Mobile Information Technology for Emergency Response, MobileResponse 2008. Bonn, Germany, May 29-30, 2008, Revised Selected Papers)
Keywords: Ver{\

Knowledge-free discovery of domain-specific multiword units - Ngonga Ngomo, Axel-Cyrille (Proceedings of the 2008 ACM Symposium on Applied Computing (SAC), Fortaleza, Ceara, Brazil, March 16-20, 2008)

„In jeder Sprache sitzen andere Augen“. Herta Müllers ex-zentrisches Schreiben - Eke, Norbert Otto (Unterwegs. Zur Poetik des Vagabundentums im 20. Jahrhundert)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Revised Use Case Point Method - Effort Estimation in Development Projects for Business Applications - Frohnhoff, Stephan; Engels, Gregor (Setting Quality Standards, Proceedings of the 11th International Conference on Quality Engineering in Software Technology (CONQUEST 2008), Potsdam (Germany))
Rapid and precise effort estimation of software development projects is crucial in IT industry. In a case study, the Use Case Point (UCP) method was applied to 15 commercial software development projects. The estimated efforts were compared with the incurred project efforts. We measured a standard deviation of 42 %. This is not acceptable for industrial usage. Therefore, we propose appropriate improvements of the Use Case Point method leading to significantly higher estimation accuracy with only 20 % standard deviation. The contribution of this paper is a detailed description of the improved Use Case Point method.

Coherent optoelectronics with single quantum dots - Zrenner, Artur; Ester, P; Michaelis de Vasconcellos, S; Hübner, M C; Lackmann, L; Stufler, S; Bichler, M (Journal of Physics: Condensed Matter)
The optical properties of semiconductor quantum dots are in many respects similar to those of atoms. Since quantum dots can be defined by state-of-the-art semiconductor technologies, they exhibit long-term stability and allow for well-controlled and efficient interactions with both optical and electrical fields. Resonant ps excitation of single quantum dot photodiodes leads to new classes of coherent optoelectronic functions and devices, which exhibit precise state preparation, phase-sensitive optical manipulations and the control of quantum states by electrical fields.

Quasar Enterprise - Engels, Gregor; Voß, Markus (Informatik-Spektrum)
Die Gestaltung und Weiterentwicklung großer Anwendungslandschaften gilt heutzutage als eine der größten Herausforderungen in der Softwaretechnik. Als Lösungsansatz wurde in den letzten Jahren vielfach das Paradigma einer serviceorientierten Architektur (SOA) diskutiert und insbesondere durch herstellerspezifische Technologien unterstützt. Dieser Beitrag widmet sich einer häufig vernachlässigten methodischen Herangehensweise und stellt mit Quasar Enterprise einen strukturierten und in der Praxis erprobten Lösungsansatz vor. Insbesondere werden konkrete Verfahrensbausteine für eine durchgängige Methode vorgestellt, die einem Architekten helfen, eine auf das zu unterstützende Geschäft ausgerichtete Anwendungslandschaft zu entwickeln und zu warten. Wesentliche Charakteristika von Quasar Enterprise sind der konsequente Einsatz einer serviceorientierten Herangehensweise, die Verwendung eines Architektur-Frameworks als Strukturierungsgrundlage und die Aufbereitung der Methode in Form von 20 Verfahrensbausteinen.

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Molecular dynamics simulation of defect formation and precipitation in heavily carbon doped silicon - Zirkelbach, F.; Lindner, Jörg; Nordlund, K.; Stritzker, B. (Materials Science and Engineering: B)
The precipitation process of silicon carbide in heavily carbon doped silicon is not yet fully understood. High resolution transmission electron microscopy observations suggest that in a first step carbon atoms form C Si dumbbells on regular Si lattice sites which agglomerate into large clusters. In a second step, when the cluster size reaches a radius of a fewnm, the high interfacial energy due to the SiC/Si lattice misfit of almost 20% is overcome and the precipitation occurs. By simulation, details of the precipitation process can be obtained on the atomic level. A recently proposed parametrization of a Tersoff-like bond order potential is used to model the system appropriately. Preliminary results gained by molecular dynamics simulations using this potential are presented.

Editorial: XXI. Messtechnisches Symposium des Arbeitskreises der Hochschullehrer für Messtechnik (AHMT), Paderborn, 20.--22.09.2007 - Henning, Bernd (Technisches Messen)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Mancosu, Paolo, “Mathematical Explanation: Problems and Prospects”, In: Topoi 20 (2001), 97–117 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sprachen im Konflikt: Zur diskursiven Reflexion der Galizischen Polyglossie in Lemberger Zeitungen des ausgehenden 19. Jahrhunderts - Ptashnyk, Stefaniya (Deutsch in multilingualen Stadtzentren Mittel- und Osteuropas. Um die Jahrhundert-wende vom 19. zum 20. Jahrhundert)

Significance of individuation in adult child-parent relationships - Buhl, Heike M. (Journal of Family Issues)
This study investigates the significance of adult children's individuation for the adult child—parent relationship. Following Youniss, individuation was assessed via its dimensions of both connectedness and individuality. A sample of 349 participants between 20 and 47 years of age were given questionnaires containing scales from the Network of Relationships Inventory among others. Individuation predicted satisfaction, intimacy, and conflict. The combination of connectedness and individuality did not have any impact on relationship quality. The significance of children's individuation did not differ between young and middle-aged adults.